Skin cancer risk and shade: comparing the risk of foresters with other outdoor workers. (4th June 2020) - Tizek, L.; Schielein, M.C.; Berger, U.; Ege, M.J.; Schneider, S.; Zink, A.
Abstract: Background: Keratinocyte carcinoma (KC) is an increasingly important public health problem with an especially high prevalence in outdoor workers. In contrast to other occupations, foresters spend most of their outdoor time under the shade of trees. Objectives: We aimed to compare the unique sun exposure patterns and sun protection behaviour of foresters with those of other outdoor workers and their relation to the KC risk. Methods: In July 2018, a cross‐sectional study was conducted at an international forestry fair using a questionnaire about health awareness and skin cancer screening by dermatologists to assess the prevalence of KC. Results: A total of 591 participants (78.7% male; mean age 46.8 ± 16.2 years) including 193 foresters were enrolled. Of all foresters, 72% experienced sunburns (solar erythema) within the past year and 50% of them experienced the worst sunburn during work. Foresters were most likely to often/always wear protective clothes (29.0%) but were least likely to often/always avoid midday sun (23.8%) and stay in the shade (31.1%). Having an outdoor profession or spending hours outside for leisure was negatively associated with sun protection. Skin examination revealed an overall KC prevalence of 16.7%, with 16.5% of foresters being affected. Conclusion: Despite being protected by trees, the risk of KC for foresters is comparable to that of other professional groups. Shade alone may not provide sufficient protection. Additional sun protection measures are necessary.